Impact of Social Vulnerability on Long-Term Growth Outcomes in Sutureless Versus Sutured Repair of Gastroschisis - Barry, Mark; Gozali, Aileen; Vu, Lan (European Journal of Pediatric Surgery, 2023)
Introduction The purpose of this study is to describe the long-term growth and nutrition outcomes of sutureless versus sutured gastroschisis repair. We hypothesized that weight z-score at 1 year would be affected by social determinants of health measured by the U.S. Centers for Disease Control Social Vulnerability Index (SVI).Materials and Methods We conducted a single-center retrospective review of patients who underwent gastroschisis repair (n = 97) from 2007 to 2018. Growth z-scores collected through 5 years of age and long-term clinical outcomes were compared based on the closure method and the type of gastroschisis (simple vs. complicated). Multiple regression analysis was performed to identify the impact of SVI themes and other covariates on weight for age z-score at 1 year.Results In total, 46 patients underwent sutureless repair and 51 underwent sutured repair with median follow-up duration of 2.5 and 1.9 years, respectively. Weight and length z-scores decreased after birth but normalized within the first year of life. Growth and long-term clinical outcomes were similar regardless of the closure method, while patients with complicated gastroschisis had higher rates of hospitalizations, small bowel obstructions, and additional abdominal surgeries. Using multiple regression, both low discharge weight and high SVI in the “minority status and language” theme were associated with lower weight for age z-scores at 1 year (p = 0.003 and p = 0.03).Conclusion Sutureless and sutured gastroschisis repairs result in similar growth and long-term outcomes. Patients living in areas with greater social vulnerability may be at increased risk of poor weight gain. Patients should be followed at least through their first year to ensure appropriate growth.
Keywords: gastroschisis; sutureless repair; social vulnerability; social determinants of health; growth